Sex differences in upper and lower strength and their association with body composition among university students - Pérez, Miguel A.; Urrejola Contreras, Gabriela P.; Hernández, Judith; Silva, Pamela; Torres Banduc, Maximiliano Andrés. (Korean Society for Exercise Nutrition, 2024)
[Purpose] Sex strongly influences physical performance throughout adolescence, and excess fat mass is associated with several health and performance impairments. This study aimed to evaluate whether variations in strength between men and women dependent on lean mass and body fat content. [Methods] This cross-sectional, quasi-experimental, non-probabilistic study involved 44 university students (22 men and 22 women, aged 19–29). Handgrip strength (HGS) was measured using an adjustable handgrip dynamometer, body composition was assessed using bioimpedance, and countermovement jumps (CMJ) were measured using a force platform. Data were analyzed using ANOVA to compare HGS and CMJ based on body mass, and the Pearson correlation coefficient was applied to examine the relationships between grip strength, body composition, and jump test performance. [Results] Strength is significantly higher in men compared to women, as is countermovement jump. The strength of women corresponded to over 50% of that of men, whereas the quantity of lean mass in women corresponded to 55% of that of men. We found a significant relationship between strength and lean mass. [Conclusion] This study supports the idea that both upper- and lower-body strengths are strongly influenced by lean mass, thereby contributing to sex differences. The primary factor in body composition that explains the disparities in HGS and CMJ between sexes is the proportion of fat mass to lean mass. Finally, the sex disparities observed between body composition and strength depend on lean mass content.
Keywords: Countermovement jump; Grip strength; Lean mass; Composición corporal; Sexo; Estudiantes universitarios